ChemInform Abstract: Gold(I)‐Catalyzed Diketonization of Alkynes and Its Application for the One‐Pot Synthesis of Quinoxaline Derivatives. Issue 43 (7th October 2013) - Liu, Yunkui; Chen, Xiaoling; Zhang, Jian; Xu, Zhenyuan
Abstract Gold(I)‐catalyzed reaction of alkynes with selectfluor and water as oxygen source affords 1, 2‐diketones which can also be trapped with o‐phenylenediamines to give quinoxaline derivatives.